The temporal spirit, expressiveness and nationality of contemporary Chinese painting - Yang, Guangyu (Linguistics and Culture Review, 2021)
The relevance of the study is determined by the fact that China, like Japan, took oil painting relatively recently. Japan became closely acquainted with Western technology in the 19th century, but at that time they still imposed a taboo on oil painting, the authorities in every way prevented its spread, protecting the traditions of national art. Only the 20th century allowed new trends to finally settle down. The work shows that the understanding of the European painting technology was widely represented in the imperial Celestial Empire. The article shows that the artists did not make a big problem to learn painting skills from the Europeans (originally the Portuguese). They learned the lessons, techniques and technology of European art, despite the fact that they had never had a similar school before. Separately, it is stipulated that cooperation after the formation of the USSR played a great influence on contemporary paintings. This explains the fact that many paintings by Chinese painters are very similar to Russian school of fine art. The authors determine that the Russian style, fully perceived by the PRC, was formed collectively from the Renaissance approach, with the inclusion of impressionism motifs.